Assessing Biodegradation Susceptibilities of Selected Petroleum Hydrocarbons at Contaminated Soils - Markus Heryanto Langsa (JOURNAL OF TROPICAL SOILS, 2010)
Assessing Biodegradation Susceptibilities of Selected Petroleum Hydrocarbons at Contaminated Soils (M.H. Langsa): The susceptibility to biodegradation of selected saturated hydrocarbons (SHCs), polycyclic aromatic hydrocarbons (PAHs) and asphaltenes in a Barrow crude oil and extracts isolated from soils contaminated with the Barrow crude oil at day 0 and 39 was determined. Soil samples were contaminated with a Barrow crude oil across the surface (5% w/w) as part of a mesocosm experiment in order to mimic similar conditions in the environment.  The extent of biodegradation of the Barrow oil extracted from the contaminated soils at day 0 and day 39 was assessed by GC-MS analyses of SHCs and PAHs fractions. Changes in the relative abundances of n-alkanes (loss of low-molecular-weight hydrocarbons) and pristane relative to phytane (Pr/Ph) and their diastereoisomers were determined. Changes in the diastereo-isomer ratios of Pr and Ph relate to the decrease in abundance of the phytol-derived 6(R),10(S) isoprenoids with increasing biodegradation. The percentage change in abundances of each of selected alkylnaphathalenes with time (day 0 to 39) was determined, enabling an order of susceptibility of their isomers to biodegradation. It was established that the 2-methylnaphthalene isomers (2-MN) is more susceptible to microbial attack than 1-MN isomer indicated by decreasing in percent abundance from day 0 to 39 for the 2-MN isomer. The GC-MS analyses of the original Barrow oil indicated the oil had not undergone biodegradation. When this oil was used in the soil mesocosm experiments the oil was shown to biodegrade to about a level 2 -3 based on the biodegradation susceptibility of the various SHCs and PAHs described above.